IMPLEMENTASI PELAYANAN E-BANKING DI ERA DIGITAL PADA BANK SYARIAH INDONESIA - Putri, Asri Oktama; Fasa, Muhammad Iqbal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Technological advances in various fields, including banking, require banks to implement electronic banking products or what is called E-Banking in order to serve their customers better. E-Banking is a banking service for obtaining information, communicating and processing banking transactions via the Internet. It is also always available, so if there is a problem there is no doubt that the customer can immediately contact their local bank, who will usually immediately confirm the service, which more or less takes up to 3 days, not even days. This research uses descriptive methods. The data collection method in this research uses document analysis, namely a qualitative descriptive method, and the writing method uses an inductive method which is descriptive and qualitative analysis. Data sources consist of secondary data. The research findings conclude that the implementation of E-Banking Services in Indonesian sharia banks includes many features that make it easier for customers to check balances, transfer money between banks or different banks, make payments, make purchases, schedule transactions, send emails, open accounts, share Ziswaf and others. refill wallet. There are several policies listed in Bank Syariah Indonesia to make customer transactions easier. This is mutually beneficial for customers and bank.Keywords: Service, E-Banking